First TDAE Reactivity Using Benzonitrile Derivatives as Substrates and Its Application to the Synthesis of 3-Substituted Isochroman-1-ones - Khoumeri, Omar; Terme, Thierry; Vanelle, Patrice (Synthesis, 2018)
The first TDAE-initiated reaction between benzonitrile derivatives as substrates and substituted benzaldehydes to form substituted hydroxyethylbenzonitrile derivatives is reported. The 2-hydroxyethyl benzonitrile derivatives thus formed were good candidates for one-pot lactonization in a mixture of hydrochloric acid and methanol at 70 °C over five hours. These reactions furnished the corresponding 3-substituted isochroman-1-one derivatives in good yields.
Keywords: TDAE; benzonitrile; benzaldehydes; one-pot lactonization; isochroman-1-one